Evaluasi Pembelajaran Al-Qur’an Bagi Lansia Di Madrasah Diniyah Sullamus Saniyah Desa Bincau Martapura (Perspektif Al’qur’an Dan Teori Geragogy) - Masruddin Masruddin; Nuril Huda; Dina Hermina (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
The condition of learning the Koran for the elderly at Madrasah Diniyah Sullamus Saniyah has had its ups and downs. This fact is marked by the increasing and decreasing number of elderly students participating in the learning process at this Madrasa. Ironically, they stopped following the Koran learning process when their religious and spiritual condition improved. In the perspective of the Koran and research,the most central age-related decline is a reduction in cognitive speed, where the reaction time of parents is slower than the reaction time of young people.This study seeks to critically assess the Al-Qur'an learning design for the elderly at Madrasah Diniyah Sullamus Saniyah Bincau Martapura Village. The results showed that the Al-Qur'an learning design implemented for the elderly at Madrasah Diniyah Sullamus Saniyah did not pay attention to the needs and suitability of the conditions of the elderly. This can be seen from the learning objectives that seem without needs analysis. On this basis, an absolute evaluation must be carried out so that learning the Koran for the elderly at Madrasah Diniyah Sullamus Saniyah can be changed and perfected in a sustainable manner.